OPTION SPREAD TRADING STRATEGIES : SHORT POSITION ANALYSIS - Aini, Mutiara
Option is one of the nancial instruments which can be organized in the portfolio becoming an option strategy. In this nal project will be discussed ve options strategy called the options spread from the seller's point of view. Of each strategy will be determined the optimum strike price and strike date by using the "Non- dominated Sorting Genetic Algorithm: NSGA II" so the combination used in option strategy will maximize the prots and minimize the risks. Prot measuring method used is the average prot and risk measuring method used is Conditional Value at Risk. The Risks Value obtained from this combination can be used as a reference for the seller to see how big the losses suered from each sold option strategy. So sellers can anticipate the losses.